KNOWLEDGEPOINTTM: Developing within uPortal framework intuitive and personalized gateway to access and to integrate faculty-specific information and applications with unstructured data / Ahmad Izzuddin Yusof - Yusof, Ahmad Izzuddin (2005)
Portal framework offers knowledge sharing and concept of codes innovation and also a reusable coding concept for rapid application development. Portal integration is essential to enable different data, resources and services to be collected together to produce single view for large community such as FTMSK. To enable such integration, Single Sign-On solution must be develop to give easiness for user to use different application with a single place of view. This research project is prepared for the Faculty of Information Technology and Quantitative Science, MARA University of Technology, Shah Alam, is an explanatory studies on integration and Single Sign-On issues. The research address the problem related the need of seamless integration and Single Sign-On features to navigate user throughout their personalized content retrieval. This thesis provides the descriptive of several integration methods that can be implemented in FTMSK. The degrees of possibility of each method to be implemented in FTMSK are pointed out to provide an insight of the nature of the issues. This thesis also provides a prototype of integration between uPortal and Open ACS framework as a proof of concept to support the hypothesis of the research.